2023
DOI: 10.2147/idr.s401473
|View full text |Cite
|
Sign up to set email alerts
|

oprL Gene Sequencing, Resistance Patterns, Virulence Genes, Quorum Sensing and Antibiotic Resistance Genes of XDR Pseudomonas aeruginosa Isolated from Broiler Chickens

Abstract: Background: Pseudomonas aeruginosa is incriminated in septicemia, significant economic losses in the poultry production sector, and severe respiratory infections in humans. This study aimed to investigate the occurrence, oprL sequencing, antimicrobial resistance patterns, virulence-determinant, Quorum sensing, and antibiotic resistance genes of P. aeruginosa retrieved from broiler chickens. Methods: Two hundred samples were collected from 120 broiler chickens from broiler farms at Ismailia Governorate, Egypt. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Previously, Algammal et al reported 28.3% prevalence of P . aeruginosa in broiler chickens in Egypt [ 41 ] whereas El-Tawab et al found that 34% of the tested frozen fish possessed P . aeruginosa [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Algammal et al reported 28.3% prevalence of P . aeruginosa in broiler chickens in Egypt [ 41 ] whereas El-Tawab et al found that 34% of the tested frozen fish possessed P . aeruginosa [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The isolation rate of various water samples may fluctuate depending on the source and size of the sample, as well as the time and length of sample collection [3, 35, 39]. Previously, Algammal et al reported 28.3% prevalence of P. aeruginosa in broiler chickens in Egypt [40] whereas El-Tawab et al found that 34% of the tested frozen fish possessed P. aeruginosa [41]. Detection of P. aeruginosa in poultry and associated environment is alarming because of the possibilities of transmission of these pathogens to human.…”
Section: Discussionmentioning
confidence: 99%
“…The matrix is composed of three exopolysaccharides (Pel, Psl, and alginate), as well as extracellular DNA and proteins. These bacterial biofilm populations are usually resistant to antibiotic treatment and human immunity [ 21 ].…”
Section: Significance Biofilm Formation In P Aeruginosamentioning
confidence: 99%
“…Foot infection in diabetics and others with poor microvascular circulation; ear infection, particularly otitis externa and chronic suppurative otitis media, which is related with tissue damage and water obstruction; and keratitis, which is associated with prolonged contact lens usage and contaminated contact lenses. Other rare but deadly infections include endocarditis occurring in people with or without injectable drug use, and meningitis linked with penetrating trauma to the head, insertion of a CNS shunt (such as a ventriculoperitoneal (VP) shunt), or post-neurosurgical operations [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%